Effect of stress path, size and shape on the optimum parameters of a brittle-ductile concrete model. Issue 4 (2nd October 2017) - Labibzadeh, Mojtaba; Hamidi, Reza
Abstract: The main purpose of this study is to investigate the effects of the stress path, size and shape of the specimen, on the optimum values of the plastic input parameters of Concrete Damaged Plasticity-CDP-model of the ABAQUS software. This study concentrates on eccentricity, dilatation angle and viscosity input parameters. To finding optimum values of the mentioned parameters, an objective function which estimates the error of the model predictions was defined and tried to minimize. For evaluating the effect of the stress path on this optimization procedure, four different standard tests were simulated by the ABAQUS software: uniaxial compression, dual compression, dual-border cut specimen and three-point bending tests. For studying the effect of the size of the specimen, the three-point bending test, with three different sizes of the beam were modeled in the ABAQUS software. Furthermore, for investigating the effect of the specimen shape on the input parameters, a notched disk in a tensile stress field was modeled. Obtained results demonstrated that the path of the stress can influence significantly on the optimum values of the input parameters, while it was revealed that the CDP model can automatically take into account the size and shape effects in the simulation.